If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + 2t = -8t + 10 Reorder the terms: -10 + 2t = 10 + -8t Solving -10 + 2t = 10 + -8t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '8t' to each side of the equation. -10 + 2t + 8t = 10 + -8t + 8t Combine like terms: 2t + 8t = 10t -10 + 10t = 10 + -8t + 8t Combine like terms: -8t + 8t = 0 -10 + 10t = 10 + 0 -10 + 10t = 10 Add '10' to each side of the equation. -10 + 10 + 10t = 10 + 10 Combine like terms: -10 + 10 = 0 0 + 10t = 10 + 10 10t = 10 + 10 Combine like terms: 10 + 10 = 20 10t = 20 Divide each side by '10'. t = 2 Simplifying t = 2
| 7y(8y+3)= | | 2+ln(2x-5)=2.5 | | 4h+2=4h | | 21,99= | | -7v=-7v+4 | | 120-x=8x | | 40-x=2x | | 2(-3y+7)-3y=14 | | -6b-1=-6b | | 60-x=4x | | 50-x=4x | | 30-x=4x | | -5g=-2g-3g | | (x-2)2=(x+6)2 | | 4p-9=-9-7p | | -2y+3=-2y | | 15-8x=4x+7 | | -3m-10=-10-3m | | 3x-12x+7=6 | | 3z+y= | | 2x-3=40-1x | | 2n=8+10n | | 3y+3-4y=0 | | (5x-1)(x+2)=8x-4 | | -4+6s=6s | | 0=4k-4k | | -z+z=0 | | -8w=-6-7w | | 5c+6=5c | | 9x^2+6x+2=-6x-2 | | -d-4d=-5d | | 3x^2-12x+35=0 |